2020
DOI: 10.1002/bit.27333
|View full text |Cite
|
Sign up to set email alerts
|

Combined evolutionary engineering and genetic manipulation improve low pH tolerance and butanol production in a synthetic microbial Clostridium community

Abstract: Synthetic microbial communities have become a focus of biotechnological research since they can overcome several of the limitations of single‐specie cultures. A paradigmatic example is Clostridium cellulovorans DSM 743B, which can decompose lignocellulose but cannot produce butanol. Clostridium beijerinckii NCIMB 8052 however, is unable to use lignocellulose but can produce high amounts of butanol from simple sugars. In our previous studies, both organisms were cocultured to produce butanol by consolidated bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…C. beijerinckii NCIMB 8052 was cultivated as previously described in an anaerobic chamber (AW400SG, Electro-Tech, Co., Ltd., U.K.) for 12–24 h at 37 °C in liquid or solidified yeast extract–tryptone–glucose (YTG) medium (5 g/L of yeast extract, 5 g/L of tryptone, and 10 g/L of glucose) before fermentation or tolerance studies. All stock cultures were maintained in 20% (v/v) glycerol and frozen at −80 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…C. beijerinckii NCIMB 8052 was cultivated as previously described in an anaerobic chamber (AW400SG, Electro-Tech, Co., Ltd., U.K.) for 12–24 h at 37 °C in liquid or solidified yeast extract–tryptone–glucose (YTG) medium (5 g/L of yeast extract, 5 g/L of tryptone, and 10 g/L of glucose) before fermentation or tolerance studies. All stock cultures were maintained in 20% (v/v) glycerol and frozen at −80 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…This makes it difficult to compare the effectiveness of these different strategies. As regards their ability to lower pH limit allowing growth of a microorganism, no study reported so far was able to go beyond 0.5 pH unit, irrespective from the strategy (strain evolution/engineering) used [198,210,[216][217][218]. Results seem somehow more promising as regards to the ability of these studies to improve tolerance towards an organic acid.…”
Section: Improvement Of Acid Tolerancementioning
confidence: 99%
“…Enhancement of acid tolerance of a number of microorganisms has been obtained through different approaches, such as chemical mutagenesis [198], genome shuffling [210,211], adaptive laboratory evolution (ALE) [190,212], multiplex automated genome engineering (MAGE) [213], rational metabolic engineering [214,215], or combination of these strategies [198,216] (Table 3). Improved acid tolerance has been differently evaluated and quantified, for instance through survival at extreme pH (e.g., pH 2.5-3.0), or ability to grow/survive at more acidic pH than the wild-type strain, or increased growth rate and/or biomass production at moderately acidic pH or in presence of challenging concentration of organic acid.…”
Section: Improvement Of Acid Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…To further improve the adaptation between members of the co-culturing system, genetic engineering and adaptive evolution are adopted. For example, Wen et al [108] designed a co-culture system to produce butanol from lignocellulose by C. cellulovorans and C. beijerinckii. Butanol fermentation preferred low pH by C. beijerinckii, while C. cellulovorans cannot grow well at a pH below 6.4.…”
Section: Microbial Co-culturing Systems Constructionmentioning
confidence: 99%